(untitled) (The Agriculturists, 2010)
A study was conducted to determine the magnitude of area shifting to different crops over the years, assess the profitability of maize cultivation and to evaluate the factors determining area devotion to maize cultivation in Bangladesh. Sample survey was done in five districts capturing both favourable and drought prone production environment. Two villages under each district were chosen in consultation with local extension experts. A total of 240 farmers were finally selected for interview. Both descriptive and inferential statistics were employed in analyzing the data. Analysis indicated that the level of area shifting to MV Boro increased to 6% and 19% in drought prone and favourable area respectively during 2007-08 compared to 2003-04. Although the area under MV Aus increased marginally in drought prone area but in favourable areas the decrease was almost 16%. The area devoted to other crops like maize, ground nut, vegetables and chilli increased over the study period. The area under Aman rice increased by 2% in drought prone area but a reverse picture appeared in the favourable area i.c, the magnitude of area shifting from rice to non-rice under favourable area was negative. The per hectare costs of maize cultivation in drought prone and favourable area were similar. The net return and benefit cost ratio (BCR) in maize production were higher in favourable area compared to drought prone area. The study further indicated that, farm size, family agricultural labor and market availability were the vital determinants of area devotion to maize cultivation. Nearly 68 % of the sample farmers devoted their lands to maize production considering it as a profitable enterprise. Similarly, about 40% farmers adopted maize as an alternate crop since it involves much less irrigation cost.